THE LIMITS OF DEMOCRATIC CITIZENSHIP EDUCATION AS INITIATION: CULTIVATING RISK-TAKING THROUGH ASSOCIATION - Waghid, Yusef; Davids, Nuraan (South African Journal of Higher Education, 2016)
Much of the contemporary literature on democratic citizenship education accentuates the enactment of duties, rights, and responsibilities on the one hand, and a sense of belonging on the other hand (Nussbaum, 1997; Benhabib, 2011; Yuval-Davis, 2011). Inasmuch as such rights, responsibilities and conceptions of belonging – based on understandings of democratic citizenship education – is not necessarily pernicious to the discourse of education, it does seem to curb students’ aspirations to become ‘whatever being’ (Agamben, 1993). ‘Whatever being’ refers to whatever liberatory stance students might assume in university classrooms. This apparent minimisation of risk-taking in a university classroom vis-à-vis the cultivation of democratic citizenship education is likely to be compounded by the initiation approach to education that has been so aptly articulated by Peters (1966), Rorty (1999), and extended more recently by Biesta (2014). It is our contention that democratic citizenship education has a more promising opportunity to be realised if it were to be unconstrained by the act of initiation. Instead, such a form of education would become more risk-orientated if the notion of initiation were to be undermined.